Perancangan Sistem Kendali Otomatis Pada Model Stasiun Penebahan Studi Kasus Di PT. Perkebunan Nusantara V - PKS Sei Galuh - Galuh Leonardo Sihombing; Dodi Sofyan Arief; Amir Hamzah; Andri Andri (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Threshing station is the separation palm kernel process from the bunch by way of slamming into a rotating drum. The purpose of this research is to design an automatic control system on the threshing station model using PLC Zelio smart relay. PLC (Programmable Logic Controller) is a microprocessor based on instrument that can be programmed to control the machining process automatically. The threshing station model is a shape which resemble of threshing station palm oil mill of PT. Perkebunan Nusantara V - PKS Sei Galuh, it has been scaled 1 : 8. This design has 2 inputs namely push button to turn on and turn off of the works system, a rotary encoder sensor to detect the rotation screw conveyor, and has 3 outputs namely 3 units of DC motors. The programming language is used the ladder diagram by using the Software Zelio Soft 2. This design consist of the design of ladder diagram program, an automation control system design in the auto feeder and the rotary encoder sensor design. The result of this design is revealed that auto feeder runs automatically turn on for 60 seconds and turn off for 30 seconds, continuously. The rotary encoder sensor works with voltage is 4.4 Volt at the moment un-stunted and 0 .1 Volt when the stunted.Keywords : Automatic Control System, Threshing Station Model, PLC Zelio Smart Relay, Rotary Encoder Sensor.